The cytisine-enriched poly(3-hydroxybutyrate) fibers for sustained-release dosage form - Czerniecka-Kubicka, Anna; Skotnicki, Marcin; Gonciarz, Weronika; Zarzyka, Iwona; Jadach, Barbara; Lovecká, Lenka; Maternia-Dudzik, Karolina; Kovářová, Miroslava; Pyda, Marek; Tutka, Piotr; Sedlařík, Vladimír (International journal of biological macromolecules, 2023)
The polymeric cytisine-enriched fibers based on poly(3-hydroxybutyrate) were obtained using electrospinning method. The biocompatibility study, advanced thermal analysis and release of cytisine from the poly(3-hydroxybutyrate) fibers were carried out. The nanofibers' morphology was evaluated by scanning electron microscopy. The formation and description of phases during the thermal processes of fibers by the advanced thermal analysis were examined. The new quantitative thermal analysis of polymeric fibers with cytisine phases based on vibrational, solid and liquid heat capacities was presented. The apparent heat capacity of fibers was measured using the standard differential scanning calorimetry. The quantitative analysis allowed for the study of the glass transition and melting/crystallization process. The mobile amorphous fraction, degree of crystallinity and rigid amorphous fraction were determined depending on the thermal history of semicrystalline polymeric fibers. Furthermore, the cytisine dissolution behaviour was studied. It was observed that the kinetic of the release from polymeric nanofiber is delayed than for the marketed product. The immunosafety of the tested polymeric nanofibers with cytisine was confirmed by the Food and Drug Agency Guidance as well as the European Medicines Agency. The polymeric matrix with cytisine seems to be a promising candidate for the prolonged release formulation.
Keywords: polymery; Polymers; 3-Hydroxybutyric Acid; léky s prodlouženým účinkem; Delayed-Action Preparations; nanovlákna; Calorimetry, Differential Scanning; kyselina 3-hydroxymáselná; Nanofibers; diferenciální skenovací kalorimetrie